A rare case of extrapulmonary hamartoma on the visceral pleura treated by uniportal VATS: case report and literature review - Shaoqing Huang; Yong Xia; Jie Li (Journal of Cardiothoracic Surgery)
Abstract Pulmonary hamartomas are common. However, extrapulmonary hamartomas on the Visceral Pleura are very rare. We treated a patient with a pulmonary nodule at the left lower lobe by uniportal video-assisted thoracoscopic wedge resection, which showed a yellow nodule located on the visceral pleura. Pathology showed that the nodule contained a small amount of cartilage tissue and was diagnosed as hamartoma. Fat-coated extrapulmonary hamartomas located on the visceral pleura have not been previously documented in the literature. This article presents a case of such an extrapulmonary hamartoma.